Global research status, hotspots and prospects of ferroptosis in glioma: a scientometric analysis - Liu, Jing; He, Zefeng; An, Zhansen; Li, Shiduo; Liu, Liang; Liu, Yingzi (Frontiers in Cellular Neuroscience, 2025)
ObjectiveThe primary approach to the treatment of glioma involves surgical intervention, which is often complemented by radiotherapy, chemotherapy, and electric field therapy. Nevertheless, the prognosis for many patients remains poor. There exists an urgent necessity to identify novel replacement therapy strategies. A great breakthrough has been made in the study of ferroptosis in gliomas. The objective of this study is to conduct a systematic review of the current research status of ferroptosis in gliomas utilizing bibliometric analysis.MethodPublications related to glioma and ferroptosis from 2014 to 2025 were retrieved from the Science Core Collection (WoSCC) database. A bibliometric analysis was conducted using VOSviewer, CiteSpace, and the R package.ResultsA total of 440 publications from 38 countries, with China leading the way, were included in the analysis. The number of publications related to ferroptosis in gliomas has been steadily increasing each year. The primary research institutions contributing to this field include Central South University, Nanjing Medical University, Shandong University, and Southern Medical University. Frontiers in Oncology is the leading journal for ferroptosis research in gliomas, while Cell is the most frequently cited journal in this field. These publications were authored by 2,921 individuals. Among them, Lu Shan, Wang Xuanzhong, Chen Qianxue, Sun Qian, and Xu Yang contributed the highest number of articles, while Dixon, SJ was the most frequently co-cited author. Studying the mechanisms, targets, and immunotherapy of ferroptosis in gliomas are major topics in this field. “Oxidative stress,” “gpx4,” and “autophagy” are popular keywords in recent years. In addition, “chemotherapy” and “miRNA” are emerging topics in this field that are closely related to this study and warrant greater attention.ConclusionThis is the first bibliometric analysis of the relationship between ferroptosis and glioma conducted over the past 11 years. The analyzed studies elucidate the regulatory mechanisms of ferroptosis and its implications in cancer cells, identify emerging research hotspots and Frontiers in recent years, and offer valuable references for scholars investigating ferroptosis in glioma, thereby facilitating the exploration of novel alternative treatment options.